Gastrointestinal Protective Effect of Zizyphus xylopyrus (Retz) Willd Leaf Extract Against Indomethacin and HCl-EtOH Induced Ulcers - Jain, Shweta; Jain, Sourabh; Chauhan, Nagendra S.; Vaidya, Ankur (Current Traditional Medicine, 2019)
Background: Zizyphus xylopyrus (Retz.) Willd. (Rhamnaceae) is a straggling shrub or a small tree, armed with spines, found throughout north-western India, Pakistan and China. Methods: The aerial and root barks, leaves and fruits of Zizyphus species are used in medicine for the treatment of various diseases such as weakness, liver complaints, obesity, diabetes, skin infections, fever, diarrhea, insomnia and digestive disorders. Ethanolic extract of leaves of Zizyphus xylopyrus (Retz) Willd was prepared by solvent extraction and subjected to study the protective effect against Indomethacin and HCl-EtOH induced ulcer using Ranitidine (100 mg/kg) and Omeprazole (8 mg/kg) as standard respectively. Results: Histopathological lesions with marked disorientation of the gastric epithelium was observed in negative control, while extract treated rats showed a better protected mucosa with intact epithelium in comparison to standard treated rats. Ulcer index and percentage ulcer protection also represent protecting effects of the extract. Conclusion: Ethanolic extract of Z. xylopyrus (Retz) Willd leaves extract was found to be significantly protective against gastric ulcers.
Keywords: indomethacin